Multicentre chest computed tomography standardisation in children and adolescents with cystic fibrosis: the way forward. Issue 6 (13th April 2016) - Kuo, Wieying; Kemner-van de Corput, Mariette P.C.; Perez-Rovira, Adria; de Bruijne, Marleen; Fajac, Isabelle; Tiddens, Harm A.W.M.; van Straten, Marcel
Progressive cystic fibrosis (CF) lung disease is the main cause of mortality in CF patients. CF lung disease starts in early childhood. With current standards of care, respiratory function remains largely normal in children and more sensitive outcome measures are needed to monitor early CF lung disease. Chest CT is currently the most sensitive imaging modality to monitor pulmonary structural changes in children and adolescents with CF. To quantify structural lung disease reliably among multiple centres, standardisation of chest CT protocols is needed. SCIFI CF (Standardised Chest Imaging Framework for Interventions and Personalised Medicine in CF) was founded to characterise chest CT image quality and radiation doses among 16 participating European CF centres in 10 different countries. We aimed to optimise CT protocols in children and adolescents among several CF centres. A large variety was found in CT protocols, image quality and radiation dose usage among the centres. However, the performance of all CT scanners was found to be very similar, when taking spatial resolution and radiation dose into account. We conclude that multicentre standardisation of chest CT in children and adolescents with CF can be achieved for future clinical trials. Multicentre chest CT standardisation is necessary and feasible to maximise image quality and reduce radiation http://ow.ly/ZfsaE